1996
DOI: 10.1038/eye.1996.16
|View full text |Cite
|
Sign up to set email alerts
|

Elastic polypropylene suture in cataract surgery: Long-term follow-up

Abstract: The final part of a prospective, controlled study of elastic polypropylene suture for cataract surgery was undertaken. The aim was to determine the change in induced astigmatism at 30 months after extracapsular cataract surgery and to assess the long-term safety of the suture material. Thirty-two of 44 patients were reexamined for changes in astigmatism. The results of all examinations were subjected to vector analysis. Both the elastic polypropylene group and the nylon control group continued to show an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Suture 'cheese wiring' into the anterior chamber during and after surgery was not a frequent complication in canaloplasty, possibly resulting from the underestimated tensile strength of the TM. We did not find any difference in the frequency of cheesewiring between the 6-0 and 10-0 Prolene group, thereby indicating that neither the thickness nor the elasticity of Prolene sutures 36,37 may be relevant for this adverse event.…”
Section: Discussionmentioning
confidence: 75%
“…Suture 'cheese wiring' into the anterior chamber during and after surgery was not a frequent complication in canaloplasty, possibly resulting from the underestimated tensile strength of the TM. We did not find any difference in the frequency of cheesewiring between the 6-0 and 10-0 Prolene group, thereby indicating that neither the thickness nor the elasticity of Prolene sutures 36,37 may be relevant for this adverse event.…”
Section: Discussionmentioning
confidence: 75%
“…For example, nylon may be labile to hydrolysis and therefore may become fragile or even dissolve over time, particularly when used behind the iris. 12,13 A few studies reported on the longterm usage of nylon in the eye: for instance, although Mehta did not observe any nylon loop degradation in 418 intracapsular cataract extractions, biodegradation was found in 14 of 34 second-stage iris clips or iridocapsular implants in children and young adults. There were no side effects of biodegradation except 2 cases of glaucoma, and in 1 of these 2 cases, birefringent particles were found in the trabecular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Suture 'cheese-wiring' into the anterior chamber during and after surgery was, contrary to our expectations, not encountered even in the first cases in this series. This could be due to underestimating the resistance of the inner wall of the SC to tension, or alternatively, to the relative elasticity of the polypropylene suture, 36 or to possible relaxation of the suture knot. Early postoperative complications were mainly related to transient hyphaema, which represents refluxed blood from the venous system through the widely open canal and highly permeable TM.…”
Section: Discussionmentioning
confidence: 99%